Covid-19 infodemiology: association between google search and vaccination in Malaysian population - Kow, Ren Yi; Mohamad Rafiai, Norfazilah; Ahmad Alwi, Akmal Azim; Low, Chooi Leng; Ahmad, Muhammad Wafiuddin; Zakaria@Mohamad, Zamzuri; Zulkifly, Ahmad Hafiz (Cureus, 2022)
Background In light of the ongoing coronavirus disease 2019 (COVID-19) pandemic, vaccination is one of the most important defensive strategies in combating the severe acute respiratory syndrome coronavirus 2 (SARSCoV-2). Vaccine hesitancy or anti-vaccination attitude has become a barrier to the nationwide vaccination program, potentially sabotaging the effectiveness of vaccination. Thus far, Google Trends (GT) has been used extensively for monitoring information-seeking behavior during the pandemic. We aimed to investigate the association between Google search, the vaccination rate, the number of vaccinated and infected cases among the Malaysian population.